Perceived security, subjective norm, self-efficacy, intention, and actual usage towards e-payment among UPM students - Md Jusoh, Zuroni; Teng, Yee Jing (Zes Rokman Resources, 2019)
The purpose of this study is to examine the factors contributing to the intention to adopt e-payment among students of Universiti Putra Malaysia (UPM). This research focuses on perceived security, subjective norm and self-efficacy as the independent variables developed based on Theory of Planned Behavior (TPB). The relationships between variables with the intention to adopt e-payment are then explored in this study. Next, the correlation between intention to adopt e-payment and the actual usage of e-payment is also examined. In addition, the gender difference in the intention to adopt e-payment among UPM students is determined in this research. A total of 200 UPM students participated in this study which they are drawn by using systematic sampling. The data are collected through a set of self-administered questionnaire. The findings demonstrate that UPM students have moderate level of perceived security towards e-payment system. However, the subjective norm and self-efficacy of UPM students regarding e-payment are of high level. Meanwhile, UPM students have a high level of intention to adopt e-payment but only moderate level for the actual usage of e-payment. This study further finds out that there is no gender difference in the intention to adopt e-payment among UPM students. Lastly, the findings of this study conclude that perceived security (r=0.620, p=0.000), subjective norm (r=0.0.269, p=0.000) and self-efficacy (r=0.264, p=0.000) are significantly related to intention to adopt e-payment among UPM students. Meanwhile, the intention to adopt e-payment has strong positive effect on the actual usage of e-payment (r=0.708, p=0.000). Therefore, it will help the e-payment service providers, industry players, policy makers and consumers in determining the key predictors of intention to adopt e-payment. Future researches are recommended to also study about the adoption on business side and take into account of other factors for more comprehensive understanding on intention to adopt e-payment among consumers.